A STUDY TO ASSESS THE KNOWLEDGE AND PRACTICE ABOUT PREVENTION OF DENGUE FEVER AMONG WOMEN - C. Gholap, Manisha; R. Mohite, Vaishali; B Shinde, Mahadeo; Hiremath, Prabhuswami; Jadhav, Vaishali; Thampi, Sneha; Gavade, Tejasweeta; Rajan, Rincy (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: A descriptive study was conducted on knowledge and prevention about dengue fever among women in the semi-urban area of Koyana Vasahat, Karad.The objectives of the study were to assess the knowledge about dengue fever in women, to assess the practice of prevention of dengue fever, and to find out the association between knowledge about dengue fever and selected sociodemographic variables. Methodology: The research design used for the proposed study was a nonexperimental descriptive design; the sample size of the study was 266. A probability sampling technique was applied to select the subjects for the study. All the area of Koyana Vasahat is visited, and required information is collected, such as from homes & colonies. The schedule was prepared, and data was collected with the help of a structured questionnaire.Results: Overall Mean knowledge regarding dengue among the women was that 20.67% had not satisfactory knowledge, 20.30% had satisfactory knowledge, 33.83% had good knowledge, 17.29% had very good knowledge, and 7.89% had excellent knowledge. Total knowledge of women 62.28%. It was evident that the maximum number of women had average knowledge about dengue fever. In prevention practice, 69.54% of women knew about breeding, 87.21% of women knew about transmission by mosquitoes, 36.46% knew about using mosquito nets, and 9.39% knew about repellent creams. Women had average knowledge about the prevention of DF. There is a significant association between education and monthly income and no significant association between water drainage and the rest of the sociodemographic variables.  Conclusion: According to the study findings, women have average knowledge about prevention of dengue fever